Mushrooming of Management Schools: A Boon or a Bane (Trinity Journal of Management, IT & Media (TJMITM), 2011)
The road to graduates  The road to top corporate brass ha~t studies. With  shift of interest_ to_ managem;e flooded business  globalization, foreign_ m_vest?rs h_:h cheap skilled man  deals to a country lt~e India,_ w1 I d to a demand for  ower. This economic paradigm e . ~ore management institutes which necess~r,ly ~es not roduce quality and talent. We must look mto t is as a  ~erious matter as this leads to concentration o~ a (arge  chunk of youth opting for management ~long w1th it ~e  need to inspect and monitor the qualt~ of educa_t1on  provided and modify them if need be. It 1s emphasized  that the Management Institutes have to gear Uf!  themselves for improving quality, have to abandon thetr  short-sighted and fire-fighting approaches, and adopt a  policy of continuous improvement.
Keywords: Clutter and confusion; faculty crunch; globalization; quantitative and qualitative; relevance and opportunities; value education